Effects of Administering the Soybean Isoflavone Genistein on Alkaline Phosphatase Levels During Orthodontic Tooth Movement in Young and Old Rabbits - Suparwitri, Sri (Penerbit Universiti Sains Malaysia, 2021)
The goal of this study was to investigate differences in alkaline phosphatase (ALP) levels in young and old rabbits after administering the soybean isoflavone genistein during orthodontic tooth movement. Twelve rabbits were used and assigned to four groups (n = 3); OG (old rabbits), OGS (old rabbits + soybean), YG (young rabbits), and YGS (young rabbits + soybean). The rabbit mandibulary incisors were distalised using a nickel-titanium open coil spring (50 g force). Genistein was administered from the initial orthodontic force delivery until day 21, at a dose of 1.2 mg/kg BW once a day. ALP levels (U/mg) were measured on days 1, 7, 14, 21 after orthodontic force delivery using a UV-Vis 6300 spectrophotometer at a 405 nm wavelength. The results were analysed by one-way analysis of variance followed by Tukey's Honest Significant Difference (HSD) test (p < 0.05). The ALP levels between the young and old age groups were significantly different. ALP levels were highest in the YGS group, and significantly lowest in the OG group (p < 0.05). Moreover, the ALP level of the OGS group was significantly higher than that in the OG group (p < 0.05). In conclusion, daily consumption of soybean isoflavone genistein could enhance ALP levels during orthodontic tooth movement, particularly in older rabbits. Â© 2021 Penerbit Universiti Sains Malaysia. All Rights Reserved.